Sex, Drugs, and Impulse Regulation: A Perspective on Reducing Transmission Risk Behavior and Improving Mental Health Among MSM Living With HIV - Arends, Rachel M.; van den Heuvel, Thom J.; Foeken-Verwoert, Eline G. J.; Grintjes, Karin J. T.; Keizer, Hans J. G.; Schene, Aart H.; van der Ven, André J. A. M.; Schellekens, Arnt F. A. (Frontiers in Psychology, 2020)
Unprotected sexual contact continues to be a main cause of HIV transmission and poses certain key populations at increased risk for HIV infection. One of the populations at high risk are men who have sex with men. A subset of MSM engages in chemsex, whereby consumption of illicit drugs is used to facilitate or enhance sexual activity. This practice can have several negative consequences such as STIs (including HIV) and mental health problems (including compulsive sexual behavior, addiction, and mood disorders). In this article, we provide our perspective on the current situation that medical professionals dealing with MSM living with HIV often feel empty-handed in how to deal with these behavioral and psychological issues. Close collaboration between somatic and mental health professionals is key to address treatment needs of people living with HIV, regarding the negative consequences of chemsex and their overall quality of life. In this article, we discuss possibilities for psychological treatment, including behavioral skills training to improve impulse control and reduce compulsive sexual behaviors among MSM living with HIV who persistently engage in sexual transmission risk behavior, based on our experience with implementing such an intervention. Important barriers and facilitators for further implementation of behavioral interventions will be discussed. Reduction of HIV transmission risk behavior is needed to achieve the WHO aim to end HIV as a public health threat by 2030. We propose that close collaboration between somatic and mental health professionals and implementation of behavioral interventions for risk populations are key to achieve this goal.